Control of AHPND by phages: a promising biotechnological approach. (22nd July 2018) - Angulo, Carlos; Loera‐Muro, Abraham; Trujillo, Edgar; Luna‐González, Antonio
Abstract: Vibrio parahaemolyticus, V. campbellii, V. owensii and V. harveyi are causative agents of Acute Hepatopancreatic Necrosis Disease (AHPND) in shrimp. AHPND is recently one of the most important diseases worldwide because of the high mortality and huge economic losses in shrimp farms. Antibiotic resistance has caused concern into finding other options to fight against pathogenic bacterial diseases. Currently, the use of lytic phages has reemerged as a promising strategy to combat bacterial pathogens. Likewise, modern molecular tools have been applied to modify phages by genetic engineering to express specific antigens and antibodies. This study reviewed recent research reports in the development of phages to control Vibrio spp. infections in shrimp and discusses different specific strategies, placing them in perspective to combat AHPND.